2020
DOI: 10.1088/1361-6641/ab9ea9
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of high electron mobility transistor inspired: III-V electro-optic modulator topologies

Abstract: III-V heterostructure based high electron mobility transistors (HEMTs) offer superior performance as compared to CMOS silicon transistors owing to the high mobility in the 2D electron gas (2DEG) channel at the heterostructure interface. Gallium nitride (GaN) based HEMTs are also suitable for high power and high temperature applications. GaN has a rich offering of material properties spanning domains of non-linear optics, piezoelectric micro-electro-mechanical systems, and monolithic microwave integrated circui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…The AlGaN layer is the top layer in the HCG bar, with thickness 25 nm and refractive index of 2.15 at 1.55 µm wavelength. In our previous work [22] we have analyzed electro-optic modulation due to plasma dispersion effect of 2DEG in an AlGaN/GaN HEMT, wherein we observed that the electron wavefunctions in the 2DEG are highly localized within a distance of 10 nm at the AlGaN-GaN interface, which is also consistent with other reported calculations [42]. Therefore the thickness of the 2DEG layer in the multi-layer HCG is considered as 10 nm.…”
Section: Modeling and Simulation Setup A Analytical Model For Multi-l...supporting
confidence: 84%
See 4 more Smart Citations
“…The AlGaN layer is the top layer in the HCG bar, with thickness 25 nm and refractive index of 2.15 at 1.55 µm wavelength. In our previous work [22] we have analyzed electro-optic modulation due to plasma dispersion effect of 2DEG in an AlGaN/GaN HEMT, wherein we observed that the electron wavefunctions in the 2DEG are highly localized within a distance of 10 nm at the AlGaN-GaN interface, which is also consistent with other reported calculations [42]. Therefore the thickness of the 2DEG layer in the multi-layer HCG is considered as 10 nm.…”
Section: Modeling and Simulation Setup A Analytical Model For Multi-l...supporting
confidence: 84%
“…Even though the 2DEG layer is highly localized at the AlGaN-GaN interface, and has calculated spatial extent of merely 10 nm with small change in refractive index (3.5 × 10 −3 ) due to applied gate voltage, incorporating the HEMT into an HCG structure results in large change in reflectivity (>50 %) by switching the 2DEG from ON (saturation) to OFF (depletion) state. This boost in modulation efficiency is significant improvement from HEMT based modulator architectures presented in our previous work [22]. The HCG resonance wavelength showing a linear dependence on the GaN thickness and duty cycle (η) of the gratings.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations